How configuration theory explains performance growth and decline after Chinese firms cross-border M&A: using the fsQCA approach. Issue 4 (8th August 2022) - Cheng, Cong; Yang, Ze; He, Yining; Yan, Lulu
ABSTRACT: Mergers and acquisitions are important mechanisms for the growth of corporations, but up to now the evidence and explanations for good deals and bad deals are mixed. This study attempts to apply configuration theory to perceive and evaluate M&As holistically – that is, as a complex configuration of Timing, Environment, and People, an ideology that stems from ancient Chinese philosophers and has been spread in China for thousands of years. Overlooking the interdependent nature of the factors of Timing, Environment, and People in influencing M&As has limited our understanding of acquisition performance. Through examining the 80 largest cross-border M&A cases in Chinese listed companies by deal value between 2015 and 2018, relying on fuzzy-set methodology by using fsQCA, we investigate different configurations that lead to performance change; the result reveals two different configurations that equifinally result in post-merger performance growth, and three that decline. By constructing a typology of 'good' and 'bad' deals, we develop a mid-range theory of M&A performance change. Thus, the central contribution of this study is to help with the formation of a comprehensive understanding of M&As, and to offer novel managerial implications for practitioners.